Ukraine : First Review Under the Stand-By Arrangement, Requests for Waivers of Nonobservance and Applicability of Performance Criteria, and A Request for Rephasing of the Arrangement. (IMF Staff Country Reports; Country Report, 2014)
EXECUTIVE SUMMARY The first review discussions took place in a context of heightened geopolitical tensions and deepening economic crisis. Intensification of the conflict in the East and escalation of the gas dispute with Gazprom, two of the key risks identified at the time of the program request, have materialized. These developments have affected confidence, balance of payment flows, economic activity, and budget execution. The banking sector has had to cope with larger-than-anticipated deposit outflows, and the exchange rate has depreciated more than expected at the time of the program request. The authorities have implemented policies broadly as agreed, but significant pressures have emerged. All but one performance criteria for end-May were met and all structural benchmarks have been implemented, albeit some with a delay. However, the deterioration in the economic outlook, fiscal and quasi-fiscal pressures, and heightened balance of payment difficulties are putting the initial program targets in jeopardy. Two end-July PCs are estimated to have been missed; and the end-2014 targets are out of reach. All continuous PCs were met. Discussions focused on the appropriate policy response to these short-term pressures and on reforms to support sustained growth. There was agreement that the policy effort should focus on compensatory measures to meet key program objectives, while allowing some temporary deviations from the initial targets. In particular, the NBU will limit the decline in reserves through market purchases; the government will take additional fiscal measures to keep public finances sustainable; and Naftogaz will strengthen current and past gas bills collection. Discussions also focused on reforms aimed at modernizing the monetary policy framework, preserving financial stability, addressing governance issues and improving the business climate. Nonetheless, risks loom large. The program hinges crucially on the assumption that the conflict will begin to subside in the coming months. Should active fighting continue well beyond that, the small buffers under the revised baseline would be quickly exhausted, requiring a new strategy, including additional external financing. A further heightening of geopolitical tensions could also have significant economic consequences. Domestically, policymaking may become more difficult in case of early elections. Strong policy performance and adherence to the planned reforms is therefore critical. Staff supports the authorities' request for completion of the first review and the waivers for nonobservance and applicability of performance criteria. The purchase released upon completion of the review would be in the amount of SDR 0.914 billion, of which SDR 0.650 billion will be used to finance the budget deficit.